Effect of crude polyphenol extracted from black olive fruit (Olea europae) on male reproductive system of rats: Anwar Ibrahim Obaid¹, Layla Hashim Alol¹, Aous Kahtan Al-Mzaien², Omar Hussein Khalaf³ - Obaid, Anwar Ibrahim (The Iraqi Journal of Veterinary Medicine, 2015)
The current study was conducted to evaluate the effect of olive polyphenols (200 mg/kg) on mature reproductive performance of male rats subjected to oxidative stress by 1%hydrogen peroxide. Twenty rats were divided randomly into four equal groups and treated for 30 days to control group C which were orally adminstrated ordinary tap water, while the first group (G1) was given 1% H2O2 in drinking water, the second group (G2) was treated orally alcoholic extract of polyphenol in olive (200mg/kg) by oral intubation. The third treated group (G3) was treated orally H2O2 and black olive fruit- polyphenol. Blood samples were collected after 30 days for measuring, the serum concentration of testosterone, follicular stimulating hormone (FSH) and leuitinizing hormone (LH). At the end of experiment, the animals were scarified and testis were removed, weighed as well as section from them were taken for histopathological study and the epididymis were taken for counting dead and live sperms. The results showed a significant increase in the weight of the testis in G2 group as compared to the control and significant decrease in the percentage of live sperms in (G1) group and significant increase in the percentage of dead sperms in H2O2 treated G1 group and control group. The results show significant differences in testosterone hormone concentration between treated groups and control group while there was known significant increased in concentration of luteinizing hormone between treated groups and control group. There was a significant decrease in FSH in treated (G1) group comparing with control group. The histological study showed edema and thickness of basement membrane of seminiferous tubules with incomplete spermatogenesis process in treated (G1) group, there were no lesions observed in other treated groups. Finally, the outcomes of of this study documented the advantageous effect of crude polyphenolic compounds of olive against the harmful effect of H2O2 on reproductive system of adult males rats.